2019
DOI: 10.4269/ajtmh.18-0171
|View full text |Cite
|
Sign up to set email alerts
|

Rural South African Community Perceptions of Antibiotic Access and Use: Qualitative Evidence from a Health and Demographic Surveillance System Site

Abstract: . Knowledge and practices of rural South African populations with regard to antibiotic access and use (ABACUS) remain understudied. By using the case of four villages in the north east of the country, our aim was to investigate popular notions and social practices related to antibiotics to inform patient-level social interventions for appropriate antibiotic use. To achieve this, we investigated where community members (village residents) were accessing and sourcing medication, and what they understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…Additional factors also limited access in South Africa, including ability to reach and to pay. 14 One exception was rural Mozambique, a low-income country with a relatively small proportion of antibiotics purchased without prescription (67 [8·0%] of 839), caused not by better enforcement but rather by limited access, as well as availability of free health care provided by clinical studies to participating patients. 15 , 16 Our findings confirm the common practice of accessing antibiotics without prescriptions in LMICs that has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors also limited access in South Africa, including ability to reach and to pay. 14 One exception was rural Mozambique, a low-income country with a relatively small proportion of antibiotics purchased without prescription (67 [8·0%] of 839), caused not by better enforcement but rather by limited access, as well as availability of free health care provided by clinical studies to participating patients. 15 , 16 Our findings confirm the common practice of accessing antibiotics without prescriptions in LMICs that has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interview guide (see Additional file 1) was used to explore participants’ knowledge, attitudes and perceptions regarding antibiotics and ABR. The guide was developed based on an extensive literature review [8, 12, 13, 1723], and was validated by a panel of experts consisting of two senior academics with expertise in pharmacy practice and a senior academic with expertise in infectious diseases. Minor revisions were made according to their feedback.…”
Section: Methodsmentioning
confidence: 99%
“…To design effective educational interventions, it is essential to understand public knowledge, attitudes and perceptions regarding antibiotics and ABR [16]. Previous qualitative studies have explored public attitudes towards and perceptions of antibiotics and ABR in European countries [17], India [18], New Zealand [19], Sweden [20], Australia [21], Sri Lanka [22], South Africa [23], Albania [24], Indonesia [25] and the United Kingdom (UK) [2630]. Overall, these studies indicated that the general public and patients had inadequate knowledge and misconceptions about antibiotics and ABR.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative interviews and focus groups were held with 60 community members. They suggested the need for strong sales regulations and context-specific educational campaigns to promote the safer use of antibiotics [ 138 ].…”
Section: What Do People Know?mentioning
confidence: 99%